SOME PROPERTIES OF SELF COMPACTING FIBER REINFORCED CONCRETE - Alyousif, Ahmed; Eren, Özgür (My University, 2010)
Today many countries are producing self-compacting concrete (SCC) and it is known that SCC has many advantages compared to conventional concrete. On the other hand, it is very well known that tensile strength of concrete can be improved by adding steel fibers in concrete. Although fiber reinforced concrete (FRC) is being produced in Cyprus for a long time, SCC is a new product for construction industry. Therefore, combination of SCC & FRC would bring many benefits. This study was split into 3 parts. First part was based on the design of FRC with two different steel fiber contents by volume of concrete (namely, 0.5% and 1.0%) and three different steel fiber aspect ratios (namely, 60, 65, and 80). Second part was based on designing SCC with locally available materials of Cyprus in addition to chemical additives. The third part was based on combination of SCC and FRC with optimum proportions. Produced self-compacting fiber reinforced concrete (SCFRC) was tested for fresh mix properties such as flow spread, T50, L-box, V-funnel, and hardened properties such as compressive strength, splitting tensile strength, pundit, and concrete hammer. The results have shown that the addition of fibers increases the compressive strength and tensile strength. It is observed that aspect ratio of 80 and 65 gives better results in increasing compressive and tensile strength compared to aspect ratio of 60. It has also been found that better workability can be obtained for SCFRC by increasing w/c ratio and usage of admixture.
Keywords: Flow test; J-ring; T50; V-funnel; L-box